FILSAFAT PROGRESIVISME DAN IMPLEMENTASINYA BAGI PENDIDIKAN KEAGAMAAN KATOLIK - Anselmus Yata Mones; Siti Mositoh; Mochmad Nursalim (Bahasa Indonesia, 2023)
Progressivism philosophy is one of the schools of modern educational philosophy that offers a new approach to implementing education in a better, quality direction and provides real guidelines for educators to facilitate student learning. The essence of understanding progressivism is to provide the widest opportunity for students (students) to develop according to their abilities, and emphasize the importance of the basics of independence and freedom for students in seeking any information that supports their development. The purpose of this study is to address the implementation of the philosophy of progressivism in Catholic religious education. The researcher uses the literature review method to collect sources related to the implementation of the philosophy of progressivism in Catholic religious education. The results of research from various church documents and several studies show that teachers are still used as the only main source who must equip themselves with knowledge in order to be able to provide correct information and knowledge to students. Students have not been given the full space to explore the available learning resources. In this study there is an offer to change the pattern of learning according to the philosophy of progressivism. Through the application of the philosophy of progressivism all learning will be student-centered and democratic and independent learning activities will be realized.